Note on probable development of a Transverse Force on a Tropical Cyclone due to its interaction - SAHA, KSHUDIRAM (MAUSAM, 1965)
The paper discusses the probable development of a transverse force on a tropical cyclone due to its interaction with the steering current, By using a simplified form of the Bernoulli equation, an expression is derived for the Cross-current pressure drop and it is concluded that due to this pressure-difference effect alone a cyclone will experience a swerve to the right of Its direction of motion in the northern hemisphere, Some limitations of the treatment are pointed out.